2020
DOI: 10.1002/cssc.201903526
|View full text |Cite
|
Sign up to set email alerts
|

Lignin‐First Fractionation of Softwood Lignocellulose Using a Mild Dimethyl Carbonate and Ethylene Glycol Organosolv Process

Abstract: A mild lignin‐first acidolysis process (140 °C, 40 min) was developed using the benign solvent dimethyl carbonate (DMC) and ethylene glycol (EG) as a stabilization agent/solvent to produce a high yield of aromatic monophenols directly from softwood lignocellulose (pine, spruce, cedar, and Douglas fir) with a depolymerization efficiency of 77–98 %. Under the optimized conditions (140 °C, 40 min, 400 wt % EG and 2 wt % H2SO4 to pinewood), up to 9 wt % of the aromatic monophenol was produced, reaching a degree of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
91
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 82 publications
(96 citation statements)
references
References 60 publications
4
91
0
1
Order By: Relevance
“…The same group also compared the effect of different metal triflates [M(OTf)x] on the yield of C 2 ‐aldehydes using β‐O‐4 model compounds, finding that the metal triflates Bi(OTf) 3 , Fe(OTf) 3 , and Hf(OTf) 4 showed the most promising cleavage efficiency to form C 2 ‐aldehdyes with Fe(OTf) 3 giving the highest yield (19.3 wt %) of phenolic C 2 ‐aldehydes . Recently, a mild hydrogenolysis method using H 2 SO 4 was developed with dimethyl carbonate (DMC) as solvent and ethylene glycol as stabilization agent, achieving 77–98 % yield of C 2 ‐acetal phenolic monomers …”
Section: Other Strategies For Improving the Monomer Yields And Potentmentioning
confidence: 99%
“…The same group also compared the effect of different metal triflates [M(OTf)x] on the yield of C 2 ‐aldehydes using β‐O‐4 model compounds, finding that the metal triflates Bi(OTf) 3 , Fe(OTf) 3 , and Hf(OTf) 4 showed the most promising cleavage efficiency to form C 2 ‐aldehdyes with Fe(OTf) 3 giving the highest yield (19.3 wt %) of phenolic C 2 ‐aldehydes . Recently, a mild hydrogenolysis method using H 2 SO 4 was developed with dimethyl carbonate (DMC) as solvent and ethylene glycol as stabilization agent, achieving 77–98 % yield of C 2 ‐acetal phenolic monomers …”
Section: Other Strategies For Improving the Monomer Yields And Potentmentioning
confidence: 99%
“…[13] Am ild organosolv extraction of lignin subsequentt oh ydrothermal pretreatment was recently reported. [14] Evenm ore recently,p olyhydroxy alcohols, such as butanediol [15] and ethylene glycol in combination with dimethyl carbonate, [16] have been used in the reactived issolution of biorefinery lignins.…”
Section: Introductionmentioning
confidence: 99%
“…Liquid alkylcyclohexanes, arenes, polyols, and furfural derivatives were produced [70,71]. The latest novel results were carried out using new catalysts [80,87,88] and by developing task-specific catalysts for hardwood and softwood [86], chemodivergent hydrogenolysis (for propyl-or propanol-methoxyphenol production) [87], membrane filtration [83], and applying new solvents/stabilization agent (dimethyl carbonate) [92]. The first integrated techno-economic assessment of a biorefinery process revealed that using only waste wood as feedstock can make the investment profitable [101].…”
Section: Discussionmentioning
confidence: 99%
“…Softwood lignocellulose was effectively (77-98%) depolymerized in a mild lignin-first acidolysis process (140 • C, 40 min, entry 73 in Table 1) using dimethyl carbonate and ethylene glycol solvents/stabilization agent producing high yield (9 wt %) of aromatic monophenols (2020, second row in Figure 4) and preserving cellulose as evidenced by a 85% glucose yield after enzymatic digestion [92]. The total utilization of lignin and carbohydrates in eucalyptus towards phenolics, levulinic acid, and furfural was emphasized in another paper in 2020: Pd/C catalyst in methanol solvent was used in the hydrogenolysis step, 50 wt % maximum phenolic monomers yield was achieved (entry 74 in Table 1) [93].…”
mentioning
confidence: 99%